Afghanistan - Ebertowski, Monika 1952- (Braunschweig Westermann, 2010)
"An overview of the history, geography, government, economy, language, people, and culture of Afghanistan. Includes numerous color photos, a detailed map, useful facts, and detailed resource section"--Provided by publisher
Literaturangaben
Archivierung/Langzeitarchivierung gewährleistet
Archivierung prüfen
***Themenheft***
Keywords: Afghan War, 2001- -- Juvenile literature; Afghan War, 2001- -- United States -- Juvenile literature; Afghanistan -- Politics and government -- 2001- -- Juvenile literature; Lehr- und Lernressource; Aufsatzsammlung